2004
DOI: 10.1063/1.1760512
|View full text |Cite
|
Sign up to set email alerts
|

Higher order and infinite Trotter-number extrapolations in path integral Monte Carlo

Abstract: Improvements beyond the primitive approximation in the path integral Monte Carlo method are explored both in a model problem and in real systems. Two different strategies are studied: The Richardson extrapolation on top of the path integral Monte Carlo data and the Takahashi-Imada action. The Richardson extrapolation, mainly combined with the primitive action, always reduces the number-of-beads dependence, helps in determining the approach to the dominant power law behavior, and all without additional computat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
47
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 30 publications
5
47
0
Order By: Relevance
“…Working directly on the exponential of the Hamiltonian, Takahashi and Imada 10 introduced in the action the double commutator [[V ,K],V ] and showed that the new algorithm (TIA) was of fourth order. As showed in previous work, 24 the TIA reduces significantly the number of beads to reach the asymptotic limit and therefore it can be very useful in quantum systems if the temperature is not very small. However, if one is interested on achieving lower temperatures, deep in the quantum regime, the TIA is still not accurate enough since the number of beads required is yet too large.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…Working directly on the exponential of the Hamiltonian, Takahashi and Imada 10 introduced in the action the double commutator [[V ,K],V ] and showed that the new algorithm (TIA) was of fourth order. As showed in previous work, 24 the TIA reduces significantly the number of beads to reach the asymptotic limit and therefore it can be very useful in quantum systems if the temperature is not very small. However, if one is interested on achieving lower temperatures, deep in the quantum regime, the TIA is still not accurate enough since the number of beads required is yet too large.…”
Section: Discussionmentioning
confidence: 84%
“…As in our previous work, 24 we have studied the accuracy of the CA in a fully many-body calculation, deep in the quantum regime, as it is liquid 4 He. We consider a bulk system at a density ρ = 0.02186Å −3 and at two temperatures, T = 5.1 and 0.8 K. The calculation is performed within a simulation box of 64 atoms with periodic boundary conditions and with an accurate Aziz potential.…”
Section: Liquid 4 Hementioning
confidence: 99%
See 2 more Smart Citations
“…In the primitive approximation of path integral, the dependence of the integrated quantities such as the energy on the number of beads , is scaled as [41] = 0 + 2 −2 + 4 −4 + ⋯…”
Section: Richardson Extrapolationmentioning
confidence: 99%